2018
DOI: 10.1103/physrevd.98.103023
|View full text |Cite
|
Sign up to set email alerts
|

Probing the dark matter-electron interactions via hydrogen-atmosphere pulsating white dwarfs

Abstract: In Phys. Rev. D 98, 103023 (2018), a novel scenario was proposed to probe the interactions between dark matter (DM) particles and electrons, via hydrogen-atmosphere pulsating white dwarfs (DAVs) in globular clusters. The estimation showed that the scenario could hopefully test the parameter space: 5 GeV < ∼ mχ < ∼ 10 4 GeV and σχ,e > ∼ 10 −40 cm 2 , where mχ is the DM particle's mass and σχ,e is the elastic scattering cross section between DM and electron. In this comment, we have determined the exact lower li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Other independent detection strategy is needed to distinguish the excess in the CREs spectrum which can also be produced from some astrophysical sources [16,17,127]. Our recent works [128] proposed a novel scenario to probe the interaction between DM particles and electrons with 5 GeV < ∼ m χ < ∼ 10 TeV.…”
Section: Discussionmentioning
confidence: 99%
“…Other independent detection strategy is needed to distinguish the excess in the CREs spectrum which can also be produced from some astrophysical sources [16,17,127]. Our recent works [128] proposed a novel scenario to probe the interaction between DM particles and electrons with 5 GeV < ∼ m χ < ∼ 10 TeV.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, if the 1.4 TeV peak signal was proved to be correct, we do need a local source of high energy CREs. Other experiment is needed as a cross check if such signal arises from DM annihilation, for example, our recent work [119] proposed a novel scenario to probe the interaction between DM particles and electrons for the DM mass range 5 GeV < ∼ m χ < ∼ 10 TeV. In summary, with the simplicity and naturalness physics principle, we proposed that there exists the −2σ, +2σ, and −1σ deviations due to statistical fluctuations for the 1229.3 GeV bin, 1411.4 GeV bin, and 1620.5 GeV bin of the DAMPE data.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, Niu et al, (2018) have considered the presence of a DAV star with the same characteristics as G117-15B in the cluster ω-Cen assuming the DM properties proposed by Amaro-Seoane et al, (2016) and have found that the secular drift of the pulsations could provide interesting bounds to the WIMP properties.…”
Section: Weakly Interacting Massive Particlesmentioning
confidence: 99%